Compositional features of the “Kweli” red raspberry and its antioxidant and antimicrobial activities - Vara, Ana Luísa (2018)
Red raspberries (Rubus idaeus L.) are increasingly popular foods in contemporary diets due to their freshness, nutritional value and health claims. Among the existing cultivars, “Kweli” is one of the most productive and widely cultivated. In this study, the nutritional value and chemical composition of “Kweli” red raspberry were characterized by the official method of food analysis and chromatographic techniques, and its antioxidant and antimicrobial activities were tested against biological/biochemical oxidizable substrates and foodborne bacteria and fungi strains, respectively. Carbohydrates (including fructose and glucose, 14.3 and 12.6 g/100 g dw, respectively), proteins (6.8 g/100 g dw), and ashes (3.90 g/100 g dw) were major constituents. The fat content was quite low and constituted mainly by unsaturated fatty acids (58.3%), with a predominance of oleic acid. Fresh red raspberry also contained high levels of citric (2.7 g/100 g) and ascorbic (17 mg/100 g) acids. The anthocyanins (4.51 mg/g extract) cyanidin-O-hexoside and mostly cyanidin-O-sophoroside were identified in the red raspberry hydroethanolic extract, which was able to inhibit thiobarbituric acid reactive substances (TBARS) formation (EC50 of 122 µg/mL), oxidative hemolysis (IC50 of 298 µg/mL), and β-carotene bleaching (EC50 of 18.7 µg/mL). In turn, the extract was more effective than the food additive E224 against Bacillus cereus. All these results highlighted the nutritional quality of “Kweli” red raspberry and showed some compositional differences in relation to other cultivars. Therefore, its inclusion in a daily diet can be helpful to obtain nutrients and antioxidants and bring health benefits.